Transcriptomic and Metabolomic Analysis Provides Insights into the Fruit Quality and Yield Improvement in Tomato under Soilless Substrate-Based Cultivation - Jinghua Guo; Lingdi Dong; Shyam L. Kandel; Yonggang Jiao; Linqi Shi; Yubo Yang; Ainong Shi; Beiquan Mou (Agronomy, 2022)
The effects of soilless substrate-based versus soil cultivation on overall fruit quality and yield in tomato (Solanum lycopersicum) were studied using the tomato cv. Zhonghua Lvbao. Experiments for tomato soilless cultivation were carried out under greenhouse conditions. Plant growth, fruit quality and yield, and physiologic traits were observed. RNA-seq and RT-PCR, as well as metabolomic analyses were performed to examine the expressed genes and metabolites under soilless substrate cultivation. The results showed that the plant height, stem diameter, and chlorophyll contents of tomato under substrate-based cultivation were increased by 37.3%, 19.8%, and 15.3%, respectively, compared with soil cultivation system. Leaf photosynthetic and transpiration rates, stomatal conductance, and root vitality of tomato, under substrate-based cultivation, increased by 29.0%, 21.2%, 43.9%, and 84.5%, respectively, compared with soil cultivation. The yield reached 7177.5 kg/667 m2, and the relative yield increased by 10.1%, compared with soil cultivation. The contents of total soluble sugar, soluble solids, and vitamin C increased by 35.7%, 19.7%, and 18.2%, respectively, higher than those of soil cultivation in tomato fruits, while nitrate content and titratable acid decreased by 29.4% and 11.8%, respectively. Therefore, substrate-based-cultivation can increase production and improve tomato fruit quality and taste. We examined the expressed genes and metabolites to explore the molecular mechanism of plant growth and overall fruit quality improvement in substrate-based cultivation. A total of 476 differentially expressed genes were identified by transcriptomes profiling, of which 321 and 155 were significantly up- and down-regulated, respectively. The results of metabolomics analysis showed that 441 metabolites were detected, where 24 and 36 metabolites were up- and down-regulated, respectively. By combining analyses of transcriptomic and metabolic groups, genes and metabolites related to the fruit quality were mainly concentrated in the vitamin B6/ascorbic acid/aldonic acidmetabolism, and glycerophospholipid metabolic pathways. Therefore, substrate-based cultivation can elevate vitamin and soluble sugar contents and the expression of fruit flavor related genes, which lays an initial background for exploring the mechanism of substrate-based cultivation, in order to improve the quality of tomato in the future.